UJI EFEKTIVITAS ANTIBAKTERI KOMBINASI EKSTRAK ETIL ASETAT DAUN RIMBANG (Solanum torvum Sw.) DAN DAUN KECOMBRANG (Etlingera elatior (Jack) R.M.sm.) TERHADAP Staphylococcus Aureus dan Escherichia Coli - Samosir, Sri Rezeki; Siagian, Hartika; Purba, Sefniarta (JIFI (Jurnal Ilmiah Farmasi Imelda), 2024)
The rimbang plant is one of the traditional plants used in the treatment of infectious diseases. The kecombrang plant has long been known and used by the public, several studies have shown that kecombrang flowers and leaves have antibacterial activity against gram-positive and gram-negative bacteria. To determine whether the combination of rimbang leaf extract and kecombrang leaf has antibacterial effectiveness against Staphylococcus aureus and Escherichia coli bacteria, use the disc method. Ethyl acetate extract of rimbang leaves and kecombrang leaves is made by maceration. The ethyl extract of rimbang leaves and kecombrang leaves was screened for phytochemical compounds. Antibacterial activity was tested using the paper disc diffusion method with varying concentrations of 30%, 40% and 50%. The results of screening for phytochemical compounds show that rimbang leaf extract contains alkaloids, terpenoids, flavonoids and tannins. Meanwhile, the results of screening for phytochemical compounds in kecombrang leaf extract contain alkaloids, saponins, flavonoids and tannins. The antibacterial effectiveness test of the combination of rimbang leaf and kecombrang leaf extracts from 3 concentration variations, namely 30%, 40% and 50%, has antibacterial effectiveness against staphylococcus aureus and Escherichia coli, the most effective concentration for staphylococcus aureus bacteria is at a concentration of 30% with a ratio of 3 :1 with a result of (13.2) while Escherichia coli bacteria were found at a concentration of 30% with a ratio of 1:3 with a result of (10.3). The combination of ethyl acetate extract of rimbang leaves (Solanum torvum Sw.) and kecombrang leaves (Etlingera elatior (Jack) R.M.sm.) has been proven to have antibacterial effectiveness against Staphylococcus aureus and Escherichia coli bacteria. Based on the one way ANOVA data analysis test, there is a significant difference in antibacterial inhibition power.